Dual Solutions on Thermosolutal Marangoni Forced Convection Boundary Layer with Suction and Injection. (23rd January 2011) - Hamid, R. A.; Arifin, N. M.; Nazar, R.; Ali, F. M.; Pop, I.
Abstract : This paper considers the extended problem of the thermosolutal Marangoni forced convection boundary layer by Pop et al. (2001) when the wall is permeable, namely, there is a suction or injection effect. The governing system of partial differential equations is transformed into a system of ordinary differential equations, and the transformed equations are solved numerically using the shooting method. The effects of suction or injection parameterf 0 on the velocity, temperature, and concentration profiles are illustrated and presented in tables and figures. It is shown that dual solutions exist for the similarity parameterβ less than 0.5.